2008
DOI: 10.1152/ajpendo.00521.2007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased clearance of serum retinol-binding protein and elevated levels of transthyretin in insulin-resistantob/obmice

Abstract: Decreased clearance of serum retinol-binding protein and elevated levels of transthyretin in insulin-resistant ob/ob mice. Am J Physiol Endocrinol Metab 294: E785-E793, 2008. First published February 19, 2008 doi:10.1152/ajpendo.00521.2007.-Serum retinol-binding protein (RBP4) is secreted by liver and adipocytes and is implicated in systemic insulin resistance in rodents and humans. RBP4 normally binds to the larger transthyretin (TTR) homotetramer, forming a protein complex that reduces renal clearance of RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 57 publications
5
88
2
1
Order By: Relevance
“…However, brain RBP4 protein levels tended to be higher in APP/PSEN1 mice on chow diet and significantly higher in PSEN1 and APP/PSEN1 mice on HFD, suggesting that increased RBP4 levels may be another mechanism by which Alzheimer's disease genotype predisposes to diet-induced glucose intolerance. RBP4 is an adipokine that was recently found to be elevated in insulin-resistant states as well as in obesity in mice [23,39,40] and humans [41][42][43][44], although not all studies have reported this [24,45]. These data suggest that there are early markers of insulin resistance already present with the APP genotype, making these mice more susceptible to the effects of HFD feeding and associated insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…However, brain RBP4 protein levels tended to be higher in APP/PSEN1 mice on chow diet and significantly higher in PSEN1 and APP/PSEN1 mice on HFD, suggesting that increased RBP4 levels may be another mechanism by which Alzheimer's disease genotype predisposes to diet-induced glucose intolerance. RBP4 is an adipokine that was recently found to be elevated in insulin-resistant states as well as in obesity in mice [23,39,40] and humans [41][42][43][44], although not all studies have reported this [24,45]. These data suggest that there are early markers of insulin resistance already present with the APP genotype, making these mice more susceptible to the effects of HFD feeding and associated insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…The lipocalin retinol-binding protein 4 (RBP4) and lipocalin-2 are elevated in obese humans, correlating with lower insulin sensitivity [25,26]. Likewise, circulating concentrations of RBP4 and lipocalin-2 are elevated in obese mice [26,27]. Transgenic overexpression of RBP4 in normal mice decreases insulin sensitivity, whereas genetic ablation of RBP4 improved insulin sensitivity [28].…”
Section: Discussionmentioning
confidence: 99%
“…These studies are supported by the fact that patients with end-stage kidney failure have significantly higher circulating RBP4 levels than healthy controls and that serum creatinine levels independently predict RBP4 concentrations in both controls and patients with kidney failure (81). There is an ongoing debate on the possible influence of transthyretin on circulating RBP4 levels via RBP4's decreased renal clearance (24,25). It is also proposed that imbalance between RBP4 and retinol might be the underlying cause for the observed association between RBP4 levels and systemic insulin resistance (22).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancementioning
confidence: 97%
“…Formation of a complex with transthyretina carrier of thyroid hormone and retinol -prevents glomerular filtration of RBP4 and its subsequent excretion through the kidney (23). It is debatable whether increased transthyretin levels and/or enhanced RBP4 to transthyretin interaction can result in decreased renal clearance of RBP4 and consequently its increased circulating levels (24,25). Circulating RBP4 levels are also influenced by iron and ferritin status as discussed later in the text (26).…”
Section: Characteristics Of Rbp4mentioning
confidence: 99%